2011
DOI: 10.1017/s0145553200011573
|View full text |Cite
|
Sign up to set email alerts
|

What's Left of Leftism?

Abstract: A novel brand of laissez-faire that lay outside the political mainstream in the early postwar years was broadly hailed at the dawn of the twenty-first century as the common sense of a global age. Yet how to understand neoliberalism as a specifically political thing, especially in the unlikely terrains of Western European and leftist politics, is unclear. This article mobilizes field theory to conceptualize and investigate neoliberal politics in Western democracies, treating the left-right axis as a variable bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Many observers agree that such a 'vibrant clash' has largely disappeared from European party systems. This is reflected most famously by the cartelisation argument of Mair (1995, 2009), but also by findings that many former working-class parties have converged to neoliberal policies (Mudge 2011;Schumacher 2012). And indeed, many contributions on the effects of polarisation (to which we return below) have shown that ideological differences between parties generally facilitate citizens' participation (e.g., Dalton 2008Dalton , 2010.…”
Section: Can Anti-elite Rhetoric Decrease Income Gaps In Efficacy?mentioning
confidence: 89%
See 1 more Smart Citation
“…Many observers agree that such a 'vibrant clash' has largely disappeared from European party systems. This is reflected most famously by the cartelisation argument of Mair (1995, 2009), but also by findings that many former working-class parties have converged to neoliberal policies (Mudge 2011;Schumacher 2012). And indeed, many contributions on the effects of polarisation (to which we return below) have shown that ideological differences between parties generally facilitate citizens' participation (e.g., Dalton 2008Dalton , 2010.…”
Section: Can Anti-elite Rhetoric Decrease Income Gaps In Efficacy?mentioning
confidence: 89%
“…We depart from the general notion that some elite dissent is important for democracies (Schattschneider 1960). This is reflected most famously by the cartelisation argument of Mair (1995, 2009), but also by findings that many former working-class parties have converged to neoliberal policies (Mudge 2011;Schumacher 2012). By contrast, '[t]oo much emphasis on consensus and the refusal of confrontation lead to apathy and disaffection with political participation' .…”
Section: Can Anti-elite Rhetoric Decrease Income Gaps In Efficacy?mentioning
confidence: 99%
“…If neoliberal ideas did not shape the Danish turn towards neoliberalism, this does not preclude the fact that they play a central role in the continued persistence of such policies, especially with the continued strengthening of neoclassical liberalism even under social-democratic governments in the 1990s. This points to the central role of the shifts of centre-left parties, in the institutionalisation of the tenets of neoliberalism, from direct political project to elite common sense (Cahill , 2014;Mudge , 2011). I will argue here that economic theory, both in the case of the post-war Keynesian period and in the neoclassical period seems to function in a legitimating rather than a strategic role.…”
Section: : Discussionmentioning
confidence: 82%
“…The end of the 1970s interregnum ushered in a twenty-five-year period of neoliberal dominance. With the defeat or domestication of organized labor in the 1980s and 1990s and the rise of the pro-business leaders of the third-way social democracies, 58 no alternatives could muster major support in the period. The situation, of course, changed with the financial crisis of 2008.…”
Section: The Post-2008 Interregnummentioning
confidence: 99%